A Commonly Used Photosynthetic Inhibitor Fails to Block Electron Flow to Photosystem I in Intact Systems - Fitzpatrick, Duncan; Aro, Eva-Mari; Tiwari A., Arjun (Frontiers in Plant Science, 2020)
In plant science, 2,4-dinitrophenylether of iodonitrothymol (DNP-INT) is frequently used as an alternative to 2,5-dibromo-6-isopropyl-3-methyl-1,4-benzoquinone (DBMIB) to examine the capacity of plastoquinol and semiquinone to reduce O2. DNP-INT is considered to be an effective inhibitor of the photosynthetic electron transfer chain (PETC) through its binding at the Q0 site of Cyt-b6f. The binding and action of DNP-INT has been previously characterized spectroscopically in purified Cyt-b6f complex reconstituted with Plastocyanin, PSII membranes and plastoquinone, as well as in isolated thylakoids based on its property to block MV-mediated O2 consumption. Contrary to the conclusions obtained from these experiments, we observed clear reduction of P700+ in samples incubated with DNP-INT during our recent investigation into the sites of oxygen consumption in isolated thylakoids. Therefore, we carried out an extensive investigation of DNP-INT’s chemical efficacy in isolated thylakoids and intact leaves. This included examination of its capacity to block the PETC before PSI, and therefore its inhibition of CO2 fixation. P700 redox kinetics were measured using Dual-PAM whilst Membrane Inlet Mass Spectrometry (MIMS) was used for simultaneous determination of the rates of O2 evolution and O2 consumption in isolated thylakoids and CO2 fixation in intact leaves, using two stable isotopes of oxygen (16O2,18O2) and CO2 (12C,13C), respectively. Based on these investigations we confirmed that DNP-INT is unable to completely block the PETC and CO2 fixation, therefore its use may produce artefacts if applied to isolated thylakoids or intact cells, especially when determining the locations of reactive oxygen species formation in the photosynthetic apparatus.